Dual anti-HIV mechanism of clofarabine. Issue 1 (December 2016) - Daly, Michele; Roth, Megan; Bonnac, Laurent; Maldonado, José; Xie, Jiashu; Clouser, Christine; Patterson, Steven; Kim, Baek; Mansky, Louis
Abstract Background HIV-1 replication kinetics inherently depends on the availability of cellular dNTPs for viral DNA synthesis. In activated CD4+ T cells and other rapidly dividing cells, the concentrations of dNTPs are high and HIV-1 reverse transcription occurs in an efficient manner. In contrast, nondividing cells such as macrophages have lower dNTP pools, which restricts efficient reverse transcription. Clofarabine is an FDA approved ribonucleotide reductase inhibitor, which has shown potent antiretroviral activity in transformed cell lines. Here, we explore the potency, toxicity and mechanism of action of clofarabine in the human primary HIV-1 target cells: activated CD4+ T cells and macrophages. Results Clofarabine is a potent HIV-1 inhibitor in both activated CD4+ T cells and macrophages. Due to its minimal toxicity in macrophages, clofarabine displays a selectivity index over 300 in this nondividing cell type. The anti-HIV-1 activity of clofarabine correlated with a significant decrease in both cellular dNTP levels and viral DNA synthesis. Additionally, we observed that clofarabine triphosphate was directly incorporated into DNA by HIV-1 reverse transcriptase and blocked processive DNA synthesis, particularly at the low dNTP levels found in macrophages. Conclusions Taken together, these data provide strong mechanistic evidence that clofarabine is a dual action inhibitor of HIV-1 replication that both limits dNTP substrates for viral DNA synthesis and directly inhibits the DNA polymerase activity of HIV-1 reverse transcriptase.